Taxonomic status of two populations of Bent-toed Geckos of the Cyrtodactylus irregularis complex (Squamata: Gekkonidae) with description of a new species from Nui Chua National Park, southern Vietnam - Pauwels, Olivier S. G.; Nazarov, Roman A.; Bobrov, Vladimir V.; Poyarkov, Nikolay A. (Zootaxa, 2018)
Based on genetic, morphological and chromatical comparisons we evaluate the taxonomic status of two southern Vietnamese forest-dwelling populations of the Cyrtodactylus irregularis species complex. We confirm the allocation of the population from Binh Chau—Phuoc Buu Nature Reserve (Ba Ria—Vung Tau Province) to C. cattienensis and we describe the population of Nui Chua National Park (Ninh Thuan Province) as Cyrtodactylus sangi sp. nov. This brings to 18 the number of species within the C. irregularis complex and to 41 the number of described Cyrtodactylus species recorded from Vietnam.